2015
DOI: 10.1097/wno.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cell Layer Analysis by Optical Coherence Tomography in Toxic and Nutritional Optic Neuropathy

Abstract: Decreased RGL thickness and volume detected in this study support a mechanism of RGL toxicity. RGL analysis may contribute to the diagnosis and management of toxic and nutritional optic neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
3
19
1
1
Order By: Relevance
“…Viera et al 15 reported a 34% to 40% decrease in the thickness of the retinal ganglion cell layer (compared with a control group) in eight patients with EMB-induced and nutritional optic neuropathy. 15 In the present longitudinal analysis, we also observed initial cpRNFL swelling within 3 months after symptom onset. Initial decrease of GCIPL, reflecting early axonal damage caused primarily by EMB toxicity, was more remarkable in inner locations than in outer locations.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Viera et al 15 reported a 34% to 40% decrease in the thickness of the retinal ganglion cell layer (compared with a control group) in eight patients with EMB-induced and nutritional optic neuropathy. 15 In the present longitudinal analysis, we also observed initial cpRNFL swelling within 3 months after symptom onset. Initial decrease of GCIPL, reflecting early axonal damage caused primarily by EMB toxicity, was more remarkable in inner locations than in outer locations.…”
Section: Discussionmentioning
confidence: 98%
“…Early GCIPL loss, which refers to primary axonal loss in some optic neuropathies, was previously reported. 14,15 Balducci et al 14 detected damage to the GCIPL starting 6 weeks before visual loss in Leber's hereditary optic neuropathy (LHON). Viera et al 15 reported a 34% to 40% decrease in the thickness of the retinal ganglion cell layer (compared with a control group) in eight patients with EMB-induced and nutritional optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SD-OCT analysis of the GCL is expanding in the neuro-ophthalmological field, 8 with the study of diseases such as non-arteritic ischaemic optic neuropathy, 9,10 optic neuritis, [11][12][13][14] papilloedema due to idiopathic intracranial hypertension 15 and toxic and nutritional optic neuropathy. 16 The purpose of this study is to evaluate the macular GCL and peripapillary RNFL thickness in patients with unilateral posterior cerebral artery (PCA) ischaemic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal ganglion cell (RGC) layer thinning occurs earlier than retinal nerve fibre layer (RNFL) thinning after acute optic neuropathies, and quantification of the macular RGC layer thickness may provide more valuable information on neuronal damage than RNFL thickness does [29]. Toxic optic neuropathies are primarily due to injury of the RGC layer [30]. This suggests that ganglion cell toxicity plays an important role in the development of toxic optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%